On control problem for infinite system of differential equations of second order - Ibragimov, Gafurjan; Ja’afaru, Abbas Badakaya (Universiti Putra Malaysia Press, 2013)
We study a control problem described by infinite system of differential equations of second order in the space 2 r 1l+. Control parameter is subjected to integral constraint. Our goal is to transfer the state of the system from a given initial position to the origin for finite time. We obtained necessary and sufficient conditions on the initial positions for which the problem can be solved.